Indigenous knowledges as a way to disrupt norms in physical education teacher education. Issue 2 (4th May 2017) - Whatman, Susan; Quennerstedt, Mikael; McLaughlin, Juliana
ABSTRACT: The maintenance and reproduction of prevailing hegemonic norms have been well explored in physical education teacher education (PETE). A related problem has been the exclusion of Indigenous knowledges around health and physical education (HPE) in students' experiences of HPE and PETE. The danger is that certain ways of being and becoming a PE teacher, other than the sporty, fit, healthy (and white) teacher, are excluded, positioning other preservice teachers' experiences, knowledges and ways to teach as deficient. In this paper, we discuss findings from an investigation (Australian Office for Learning and Teaching CG10-1718) into the HPE practicum experiences of Indigenous Australian preservice teachers, illustrating the resources they bring to Australian HPE and PETE through the lens of John's Dewey's notion of growth and Todd's [(2014). Between body and spirit: The liminality of pedagogical relationships. Journal of Philosophy of Education, 48 (2), 231–245] ideas of liminality of pedagogical relations. This enables us to discuss Indigenous preservice teachers' capacity in disrupting norms in HPE and fostering the liminality of the pedagogical relations in PETE.